Cognitive enhancers associated with decreased risk of injury in patients with dementia: a nationwide cohort study in Taiwan. (14th November 2017) - Chao, Pei-Chun; Chien, Wu-Chien; Chung, Chi-Hsiang; Chu, Ching-Wen; Yeh, Chin-Bin; Huang, San-Yuan; Lu, Ru-Band; Chang, Hsin-An; Kao, Yu-Chen; Yeh, Hui-Wen; Chiang, Wei-Shan; Chou, Yu-Ching; et al.
Abstract : This study aimed to investigate the associations among dementia, psychotropic medications and the risk of overall injuries. In this nationwide matched cohort study, a total of 144 008 enrolled patients ≥age of 50, with 36 002 study subjects who suffered from dementia and 108 006 controls matched for sex and age, from the Inpatient Dataset, for the period 2000–2010 in Taiwan were selected from the National Health Insurance Research Database, according to International Classification of Diseases, 9th Revision, Clinical Modification. When adjusting for the confounding factors, a Cox proportional hazards analysis was used to compare the risk of developing psychiatric disorders during the 10 years of follow-up. Of the study subjects, 6701 (18.61%) suffered injury when compared with 20 919 (19.37%) in the control group. The Cox regression analysis revealed that the study subjects were more likely to develop an injury (HR: 2.294, 95% CI=2.229 to 2.361, P<0.001) after adjusting for sex, age, monthly income, urbanization level, geographic region, and comorbidities. Psychotropic medications in the subjects with dementia were associated with the risk of injury (adjusted HR=0.217, 95% CI: 0.206 to 0.228, P<0.001). Cognitive enhancers, including acetylcholinesterase inhibitors and memantine, were associated with the risk of injury in the study subjects after being adjusted for all comorbidities and medications (adjusted HR=0.712(95% CI=0.512 to 0.925, P<0.01)). In conclusion, patients who suffered dementia had a higher risk of developing injury, and the cognitive enhancers were associated with the decreased risk of injury.